The prevention and control of avian influenza: The avian influenza coordinated agriculture project() - Cardona, C. (Poult Sci, 2009)
The Avian Influenza Coordinated Agriculture Project (AICAP) entitled “Prevention and Control of Avian Influenza in the US” strives to be a significant point of reference for the poultry industry and the general public in matters related to the biology, risks associated with, and the methods used to prevent and control avian influenza. To this end, AICAP has been remarkably successful in generating research data, publications through an extensive network of university- and agency-based researchers, and extending findings to stakeholders. An overview of the highlights of AICAP research is presented.